2014
DOI: 10.1063/1.4903952
|View full text |Cite
|
Sign up to set email alerts
|

Exciton quenching at PEDOT:PSS anode in polymer blue-light-emitting diodes

Abstract: The quenching of excitons at the poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS) anode in blue polyalkoxyspirobifluorene-arylamine polymer light-emitting diodes is investigated. Due to the combination of a higher electron mobility and the presence of electron traps, the recombination zone shifts from the cathode to the anode with increasing voltage. The exciton quenching at the anode at higher voltages leads to an efficiency roll-off. The voltage dependence of the luminous efficiency is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…To avoid the near-field quenching caused by electrode, in most LHP-LEDs a conductive poly­(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) film is selected as a spacer, which also can enhance hole injection from ITO anode (Figure b and Figure a,b). ,,, In principle, the metallic PEDOT:PSS film is also regarded as an exciton quencher because of its highly electrical conductivity and interfacial defects. , Therefore, an organic semiconductor film, e.g ., poly­(4-butylphenyldiphenylamine) (poly-TPD), with low density of charge carriers is adopted as a buffer layer to eliminate the exciton quenching caused by PEDOT:PSS. , Moreover, this organic hole transport film is supposed to enhance hole injection into the recombination zone because there is a large mismatch between the deep valence band of LHPs and the Fermi level of PEDOT:PSS. ,,, …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the near-field quenching caused by electrode, in most LHP-LEDs a conductive poly­(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) film is selected as a spacer, which also can enhance hole injection from ITO anode (Figure b and Figure a,b). ,,, In principle, the metallic PEDOT:PSS film is also regarded as an exciton quencher because of its highly electrical conductivity and interfacial defects. , Therefore, an organic semiconductor film, e.g ., poly­(4-butylphenyldiphenylamine) (poly-TPD), with low density of charge carriers is adopted as a buffer layer to eliminate the exciton quenching caused by PEDOT:PSS. , Moreover, this organic hole transport film is supposed to enhance hole injection into the recombination zone because there is a large mismatch between the deep valence band of LHPs and the Fermi level of PEDOT:PSS. ,,, …”
Section: Applicationsmentioning
confidence: 99%
“…404,1078,1082,1187 In principle, the metallic PEDOT:PSS film is also regarded as an exciton quencher because of its highly electrical conductivity and interfacial defects. 1078,1193 Therefore, an organic semiconductor film, e.g., poly(4butylphenyldiphenylamine) (poly-TPD), with low density of charge carriers is adopted as a buffer layer to eliminate the exciton quenching caused by PEDOT:PSS. 396,1078 Moreover, this organic hole transport film is supposed to enhance hole injection into the recombination zone because there is a large mismatch between the deep valence band of LHPs and the Fermi level of PEDOT:PSS.…”
Section: Applicationsmentioning
confidence: 99%
“…For the blend device, due to the reduced trap density, as well as a transition from hole‐dominated to electron‐dominated transport, the recombination zone quickly moves to the anode with increasing voltage and anode quenching becomes important. Contrary to the pristine PLED, for the blend PLED, the current efficiency therefore increases sharply at low voltage and has a roll‐off around 8 V. We have shown that, in a system with a lower trap density, the efficiency roll‐off at higher bias is due to quenching of excitons at the PEDOT:PSS anode, which quenches excitons equally efficient as the metallic cathode . To illustrate the position and spatial distribution of the recombination zone, the recombination profile is calculated for both pristine and blend PLEDs with a thickness of 300 nm at 100 A m −2 , as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…[24] To illustrate the position and spatial distribution of the recombination zone, the recombination profile is calculated for both pristine and blend PLEDs with a thickness of 300 nm at 100 A m −2 , as shown in Figure 6. The profile shows that in the blend PLED, contrary to the pristine device, only anode quenching is important.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…Such an efficiency roll-off for PLEDs is typically characteristic for quenching of excitons at the anode. 20 We speculate that the better electron injection for Ba/Al as observed in Fig. 4(b) might still lead to an excess of electrons at the MEH-PPV/F8BT interface, such that more electrons can escape the recombination region.…”
Section: -3mentioning
confidence: 88%